Analysis of some flavonoids for inhibitory mechanism against cancer target phosphatidylinositol 3-kinase (PI3K) using computational tool - Suhail, Mohd; AlZahrani, Wejdan M.; Shakil, Shazi; Tarique, Mohammad; Tabrez, Shams; Zughaibi, Torki A.; Rehan, Mohd (Frontiers in Pharmacology, 2023)
Cancer has been one of the leading causes of mortality worldwide over the past few years. Some progress has been made in the development of more effective cancer therapeutics, resulting in improved survival rates. However, the desired outcome in the form of successful treatment is yet to be achieved. There is high demand for the development of innovative, inexpensive, and effective anticancer treatments using natural resources. Natural compounds have been increasingly discovered and used for cancer therapy owing to their high molecular diversity, novel biofunctionality, and minimal side effects. These compounds can be utilized as chemopreventive agents because they can efficiently inhibit cell growth, control cell cycle progression, and block several tumor-promoting signaling pathways. PI3K is an important upstream protein of the PI3K-Akt-mTOR pathway and a well-established cancer therapeutic target. This study aimed to explore the small molecules, natural flavonoids, viz. quercetin, luteolin, kaempferol, genistein, wogonin, daidzein, and flavopiridol for PI3Kγ kinase activity inhibition. In this study, the binding pose, interacting residues, molecular interactions, binding energies, and dissociation constants were investigated. Our results showed that these flavonoids bound well with PI3Kγ with adequate binding strength scores and binding energy ranging from (-8.19 to -8.97 Kcal/mol). Among the explored ligands, flavopiridol showed the highest binding energy of -8.97 Kcal/mol, dock score (-44.40), and dissociation constant term, 𝑝𝐾 𝑑 of 6.58 against PI3Kγ. Based on the above results, the stability of the most promising ligand, flavopiridol, against PI3Kγ was evaluated by MD simulations for 200 ns, confirming the stable flavopiridol and PI3Kγ complex. Our study suggests that among the selected flavonoids specifically flavopiridol may act as potential inhibitors of PI3Kγ and could be a therapeutic alternative to inhibit the PI3Kγ pathway, providing new insights into rational drug discovery research for cancer therapy.